Family Matters : Puerto Rican Women Authors on the Island and the Mainland - Moreno, Marisel C., 1973- (Book collections on Project MUSE., 2012)
Adopting a comparative and multidisciplinary approach to Puerto Rican literature, the author juxtaposes narratives by insular and U.S. Puerto Rican women authors in order to examine their convergences and divergences. By showing how these writers use the trope of family to question the tenets of racial and social harmony, an idealized past, and patriarchal authority that sustain the foundational myth of la gran familia, she argues that this metaphor constitutes an overlooked literary contact zone between narratives from both sides. She proposes the recognition of a "transinsular" corpus to reflect the increasingly transnational character of the Puerto Rican population and addresses the need to broaden the literary canon in order to include the diaspora. Drawing on the fields of historiography, cultural studies, and gender studies, the author defies the tendency to examine these literary bodies independently of one another and therefore aims to present a more nuanced and holistic vision of this literature.